The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/jcal.12581
|View full text |Cite
|
Sign up to set email alerts
|

Digital self‐control interventions for distracting media multitasking ‐ A systematic review

Abstract: Digital distractions can interfere with goal attainment and lead to undesirable habits that are hard to get red rid of. Various digital self‐control interventions promise support to alleviate the negative impact of digital distractions. These interventions use different approaches, such as the blocking of apps and websites, goal setting, or visualizations of device usage statistics. While many apps and browser extensions make use of these features, little is known about their effectiveness. This systematic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…For older students, the ban on the use of laptops leads to absenteeism (Elliot-Dorans, 2018;according to Dontre, 2020). (Biedermann, Schneider & Drachsler, 2021). It is especially difficult to determine which content should be banned, because learners may need to communicate with their peers on a social media site or watch learning-related content on the same platform where they watch entertaining videos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For older students, the ban on the use of laptops leads to absenteeism (Elliot-Dorans, 2018;according to Dontre, 2020). (Biedermann, Schneider & Drachsler, 2021). It is especially difficult to determine which content should be banned, because learners may need to communicate with their peers on a social media site or watch learning-related content on the same platform where they watch entertaining videos.…”
Section: Discussionmentioning
confidence: 99%
“…These authors find several studies, conducted between 2009 and 2017, that speak of adverse consequences in three academic subfields: cognition, performance, reading and studying. The last, fourth paper from this group talks about digital self-control interventions, which are intended to alleviate the negative impact of digital distractions (Biedermann, Schneider & Drachsler, 2021). However, the results obtained are not very encouraging.…”
Section: Conclusion From Theoretical and Review Papersmentioning
confidence: 99%
“…Common tools for reducing digital distractions include website blockers or visualizations of one's own behavior (c.f. Biedermann et al, 2021). Habits often prevent these tools from having their desired effect.…”
Section: Extension Of the Work On Digital Self-control Interventionsmentioning
confidence: 99%
“…Multitasking has been shown to consistently impair learning, both from text (Clinton-Lisell, 2021) and lectures (Barks et al, 2011; Kuznekoff & Titsworth, 2013; Sana et al, 2013). Attempts to intervene against media multitasking like drawing awareness to distracted behaviors or restricting access to distracting websites often have limited success (Biedermann et al, 2021). Consistent with this hypothesis, one study showed that participants who watched a recorded lecture with their webcam on with their self-view visible outperformed students who watched with their webcam off (Austin et al, 2022).…”
Section: The Present Studymentioning
confidence: 99%